Метод оценки отклонений результатов выполнения судном рейса под влиянием факторов риска - Онищенко, Светлана Петровна; Вишневская, Ольга Дмитриевна (НТУ "ХПИ", 2016)
В данной статье идентифицирована система факторов риска, обуславливающих изменения результатов выполнения судном рейса. Установлено влияние указанных факторов на временные и стоимостные параметры, характеризующие работу судна в рейсе. Получено выражение суточной прибыли судна с учетом возможных отклонений временных и стоимостных параметров. Для оценки величины возможных отклонений рассматриваемых параметров предлагается подход, основанный на идее VAR-метода, представлены результаты соответствующих статистических исследований.

The system of risk factors is identified in the article. These factors lead to changes in the vessel’s voyage results: weather and climatic conditions; crew errors; management problems; problems in the organization of the vessel service; inconsistencies in the delivery process; technical problems with the vessel; changes in tariffs of port services; changes in bunker costs. The influence of these factors is determined on the time and cost (bunker costs, port charges and fees) parameters characterizing vessel operation during voyage. The influences of the time and cost parameters, as well as their deviations in the cost elements of the vessel are determined. The expression of the daily profit according to the vessel’s voyage results is obtained taking into account possible deviations of time and cost parameters. To estimate the possible deviations of considered parameters an approach based on the idea of VAR-method is proposed. This approach estimates the amount of potential deviations with a given probability on the basis of normal distribution parameters. The results of relevant statistical research are presented on the example of the travel time and laytime of the vessel, justifying the legitimacy of this method, as well as demonstrating the technique of using it.
Assessment method for deviation of the work's results for vessel under the influence of risk factors
Keywords: судно; риск; рейс; отклонения; вероятность; параметры; время; стоимость; суточная прибыль; vessel; risk; voyage; deviation; probability; parameters; time; cost; daily profit; VAR-method